DIFRATANDO EXPERIÊNCIAS FORMATIVAS DA/NA DOCÊNCIA EM EDUCAÇÃO MATEMÁTICA ATRAVÉS DE VOZES DAS CRIANÇAS - JULIANA SCHUMACKER PUDELL (2024)
The aim of this dissertation is to analyze the potential of children's narratives for a school’s practice, of mathematical education, of a teacher training process. Methodologically, we worked with the construction and operation of what we called a narrative booth, which was a welcoming space with a recorder, paper and colored pencils available to children, students in the Early Years of Elementary School, who accepted our invitation to talk about themselves, about school, about mathematics. This choice sought to shift the discussion about mathematical learning from adult theories/practices/trainings to children's speeches/movements/affects in the direction of producing epistemic justice. Basing the discussion on elaborations about childhood (with authors such as César Leite and Bianca Chisté) and epistemic injustice (with Miranda Fricker), this ongoing research is based on the destabilizations that occurred in and after work with children , which guided us in a process of problematizing this author's own teaching training in institutional courses and in professional practice. Keywords: Narratives, Childhood, Epistemic Injustice, Diffraction.